Working across Boundaries: Tutor Experiences of On-campus Networked Learning (blended with face-to-face teaching) - Roberts, Gillian (Proceedings of the International Conference on Networked Learning, 2002)
This paper reports on research undertaken in one modern Scottish university (MSU) to identify university teachers’ conceptions of and approaches to teaching campus-based students using C&ITs. 18 teachers from the business school were interviewed and their transcripts were analysed to identify their underlying conceptions and approaches to teaching generally. From this a theoretical sample of 7 teachers’ transcripts representing the range of possible conceptions of teaching were analysed in detail using qualitative software to identify their conceptions of teaching using C&ITs specifically. In addition two focus group discussions were undertaken with two different teaching teams piloting the use of a managed learning environment where teachers were asked to reflect on this experience. Data was analysed and three findings are offered. Firstly a model of teachers’ conceptions of teaching campus based students using C&ITs; secondly a model of teachers’ approaches to teaching campus based students using C&ITs and thirdly the importance of the ‘experience’ of teaching using C&ITs in influencing the formation and development of teachers’ conceptions of teaching using C&ITs.